2018
DOI: 10.26633/rpsp.2018.95
|View full text |Cite
|
Sign up to set email alerts
|

Bullying involvement and substance use among Brazilian adolescent students

Abstract: Objective Although bullying involvement has been associated with adolescent substance use, most of this evidence comes from high-income countries. Little is known about substance use among perpetrator-victims in low- and middle-income countries. This study explores the association between types of bullying involvement and adolescent substance use in Brazil. Methods Data for this cross-sectional study came from the 2015 Pesquisa Nacional de Saúde do Escolar [National Ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…School violence is a global phenomenon that occurs regardless of a country's economic development [41]. This behavior most often or almost always fits into the concept of bullying [42]. Bullying is more frequent among students who are excluded or disrespected by their peers and do not feel that they belong to the group [43].…”
Section: Discussionmentioning
confidence: 99%
“…School violence is a global phenomenon that occurs regardless of a country's economic development [41]. This behavior most often or almost always fits into the concept of bullying [42]. Bullying is more frequent among students who are excluded or disrespected by their peers and do not feel that they belong to the group [43].…”
Section: Discussionmentioning
confidence: 99%
“…35 Bullying and lack of peer support are examples of social risk factors that have a strong correlation with arousing substance use in adolescents. 36,37 Bullying in schools is a social problem that causes mental health problems. Data from Thailand's national school-based survey on bullying in Thai primary schools found that male students were slightly less likely than female students to have been bullied, accounting for 58% and 42%, respectively.…”
Section: High Occurrence Of Experiencing Mental Disorders In Malesmentioning
confidence: 99%
“…Studies conducted in Latin American countries also show findings consistent with this study. A Brazilian study (18) involving 102,301 students aged 13 to 18 found a positive correlation between the use of tobacco, alcohol, and cannabis and being a victim of bullying. A similar connection was found in an Argentine study (25) with 1,328 students aged 13 to 15, associating victimization by bullying with a higher chance of alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies conducted on this topic have originated from wealthy countries in Europe and North America, not reflecting the scenario in Latin America, even though research indicates that bullying may be even more prevalent in low-and middle-income countries (14,15). Additionally, the few studies conducted in Latin America (16)(17)(18) do not analyze a wide range of substances, restricting their focus to tobacco, alcohol, and cannabis only. This study aims not only to generate more data to address the uncertainty regarding the association between bullying and substance use in adolescence but also to investigate this association with less discussed psychoactive substances, such as crack and E-cigarettes.…”
Section: Introductionmentioning
confidence: 99%